New‐onset type 2 diabetes mellitus among patients receiving HIV care at Newlands Clinic, Harare, Zimbabwe: retrospective cohort analysis. Issue 7 (8th June 2017) - Chimbetete, Cleophas; Mugglin, Catrina; Shamu, Tinei; Kalesan, Bindu; Bertisch, Barbara; Egger, Matthias; Keiser, Olivia
Abstract: Objective: To assess the incidence and associated factors of Type 2 Diabetes Mellitus (T2DM) among people living with HIV (PLHIV) in Zimbabwe. Methods: We analysed data of all HIV‐infected patients older than 16 years who attended Newlands Clinic between March 1, 2004 and April 29, 2015. The clinic considers patients whose random blood sugar is higher than 11.1 mmol/l and which is confirmed by a fasting blood sugar higher than 7.0 mmol/l to have T2DM. T2DM is also diagnosed in symptomatic patients who have a RBS >11.0 mmol/l. Risk factors for developing T2DM were identified using Cox proportional hazard models adjusted for confounding. Missing baseline BMI data were multiply imputed. Results are presented as adjusted hazard ratios (aHR) with 95% confidence intervals (95% CI). Results: Data for 4, 110 participants were included: 67.2% were women; median age was 37 (IQR: 31–43) years. Median baseline CD4 count was 197 (IQR: 95–337) cells/mm 3 . The proportion of participants with hypertension at baseline was 15.5% ( n =638). Over a median follow‐up time of 4.7 (IQR: 2.1–7.2) years, 57 patients developed T2DM; the overall incidence rate was 2.8 (95% CI: 2.1–3.6) per 1000 person‐years of follow‐up. Exposure to PIs was associated with T2DM (HR: 1.80, 95% CI: 1.04–3.09). In the multivariable analysis, obesity (BMI>30 kg/m 2 ) (aHR=2.26, 95% CI: 1.17–4.36), age >40 years (aHR=2.16, 95% CI: 1.22–3.83) and male gender, (aHR=2.13, 95% CI: 1.22–3.72) were independently associated with the risk of T2DM. HIV‐related factors (baseline CD4 cell count and baseline WHO clinical stage) were not independent risk factors for developing T2DM. Conclusion: Although the incidence of T2DM in this HIV cohort was lower than that has been observed in others, our results show that risk factors for developing T2DM among HIV‐infected people are similar to those of the general population. HIV‐infected patients in sub‐Saharan Africa need a comprehensive approach to care that includes better health services for prevention, early detection and treatment of chronic diseases especially among the elderly and obese.